2014
DOI: 10.1186/1471-2458-14-825
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors differ between rural and urban Sweden: the 2009 Northern Sweden MONICA cohort

Abstract: BackgroundRural communities have a higher burden of cardiovascular risk factors than urban communities. In Sweden, socioeconomic transition and urbanization have led to decreased populations in rural areas and changing characteristics of the remaining inhabitants. We investigated the risk factors in urban and rural populations in Northern Sweden.MethodsThe 2009 Northern Sweden MONICA Study invited a random sample of 2,500 people, 25 to 74 years and 69.2% participated. Community size was classified as rural = <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 16 publications
2
51
1
7
Order By: Relevance
“…PWV measured from the patients was highly correlated statistically with the standard arterial stiffness parameter, confirming that PWV can be an independent predictor for CVD [5]. The standard variables for the evaluation of end-organ damage are intima-media thickness (IMT) and low estimated glomerular filtration rate according to Matsumoto et al who postulated that the measured baPWV in hypertensive patients showed the statistically significant difference when compared to the healthy controls [5,6]. Shanker et al studied the cumulative effects of various biomarkers of atherosclerosis by calculating the PWV, ASI, and AIx in asymptomatic individuals using oscillometric device [3].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…PWV measured from the patients was highly correlated statistically with the standard arterial stiffness parameter, confirming that PWV can be an independent predictor for CVD [5]. The standard variables for the evaluation of end-organ damage are intima-media thickness (IMT) and low estimated glomerular filtration rate according to Matsumoto et al who postulated that the measured baPWV in hypertensive patients showed the statistically significant difference when compared to the healthy controls [5,6]. Shanker et al studied the cumulative effects of various biomarkers of atherosclerosis by calculating the PWV, ASI, and AIx in asymptomatic individuals using oscillometric device [3].…”
Section: Introductionmentioning
confidence: 77%
“…Shanker et al studied the cumulative effects of various biomarkers of atherosclerosis by calculating the PWV, ASI, and AIx in asymptomatic individuals using oscillometric device [3]. Numerous community-based studies have been conducted to evaluate the CVD risk factors using the statistical Tukey's post hoc analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Европа. По данным исследования, проведенного в Швеции в 2009г [34] в рамках проекта MONICA (Multinational MONItoring of trends and determinants in CArdiovascular disease), регулярная физическая активность в сельской местности оказалась ниже городской -76,3% vs 82%.…”
Section: курениеunclassified
“…Европа. В Швеции в 2009г [34], распространенность АГ в сельской местности оказалась выше городской -48,7% vs 39%.…”
Section: курениеunclassified
See 1 more Smart Citation